2018
DOI: 10.1016/j.tiv.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory effects of acrolein, crotonaldehyde and hexanal vapors on human primary bronchial epithelial cells cultured at air-liquid interface

Abstract: The cytotoxicity of aldehydes was studied using human primary bronchial epithelial cells (PBEC) cultured at the air-liquid interface (ALI) or under submerged conditions. PBEC were exposed for 30min via the air phase to acrolein (0.1-1mg/m), crotonaldehyde (1.5-15mg/m) or hexanal (22-221mg/m) or under submerged conditions to acrolein (0.1 and 0.2mg/L), crotonaldehyde (1 and 2mg/L) or hexanal (10 and 20mg/L). Cell culture medium was collected 8h and 24h post-exposure and analyzed for interleukin-8 (IL-8) and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 40 publications
4
37
0
Order By: Relevance
“…Furthermore, the NPs tend to gather at one spot in the ALI cultures, possibly due to the sweeping motion of ciliated cells. Similar differences in response between the two systems also were observed with aldehyde vapors, where significant induction of cytokine release and oxidative stress occurred only in the ALI cultures (Dwivedi et al 2018).…”
Section: Functions Of Airway Epithelial Cellssupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, the NPs tend to gather at one spot in the ALI cultures, possibly due to the sweeping motion of ciliated cells. Similar differences in response between the two systems also were observed with aldehyde vapors, where significant induction of cytokine release and oxidative stress occurred only in the ALI cultures (Dwivedi et al 2018).…”
Section: Functions Of Airway Epithelial Cellssupporting
confidence: 60%
“…Such exposures not only fail to capture what happens in vivo, but also may introduce irrelevant chemical interactions, limiting the translational value of any findings (Aufderheide 2005 ; Limbach et al 2005 ; Gminski et al 2010 ; Raemy et al 2012 ; Lenz et al 2013 ; Loret et al 2016 ; Upadhyay and Palmberg 2018 ). Dwivedi and colleagues demonstrated that solubilization of chemicals in culture medium blunted the effects of three pulmonary irritants (i.e., acrolein, crotonaldehyde, and hexanal), making direct comparison between the vapor- and aqueous-phase exposures difficult (Dwivedi et al 2018 ). Furthermore, interpretation of studies on chemicals known to either react with components of culture medium (Coyle et al 2018 ) or partition into the non-bioavailable compartments of the medium, such as lipids and proteins (Gülden and Seibert 2003 ), must consider the effects of these factors on chemical bioavailability.…”
Section: Exposure Systems Used With Ali Airway Culturesmentioning
confidence: 99%
“…The list of genes assessed, and corresponding primer pairs are provided in Additional file 1 : Table S1. Total mRNA from both PBEC-ALI and PBEC-ALI/MQ and MQ only were isolated following 24 h exposure (DEP and sham) using the RNeasy Mini Kit (Qiagen; n = 6) as described previously [ 44 ]. Concentration of RNA was measured using the Nano drop (ND1000 Technology).…”
Section: Methodsmentioning
confidence: 99%
“…Toxic effects of compounds applied as vapors are increasingly tested in human primary bronchial epithelial cells cultured at the air-liquid interface (e.g. Dwivedi et al 2018).…”
Section: -Dimensional Cultures Cultures At the Air-liquid Interphasmentioning
confidence: 99%